THE NEXUS OF EXTERNAL DEBT, PRIVATE INVESTMENT AND FINANCIAL DEVELOPMENT: EVIDENCE FROM SELECTED SACU COUNTRIES - Brian Muyambiri; John-Baptiste Mabejane (Economic Review)
This paper examines the dynamic causal relationship between financial development, external debt and investment in Lesotho, Namibia and Eswatini from 1980–2020 using a multivariate Granger–causality model. The study considers trade, savings and economic growth as intermittent variables in the analysis. Adopting the autoregressive distributed lag (ARDL) bounds testing approach, the study results show that the causal relationship between financial development, external debt and investment in Lesotho, Namibia and Eswatini from 1980–2020 is country-dependent. For Eswatini, both investment and financial development Granger cause external debt, both in the short run and in the long run. However, for Lesotho and Namibia, it is the contrary, with external debt Granger causing financial development both in the short run and in the long run. The exception is Lesotho, where external debt is also found to Granger cause investment, also both in the short run and the long run. The study, therefore, concludes that for Eswatini, immense efforts in promoting investment and financial development chiefly stimulate external debt and the real sector in both the short run and the long run. For Namibia and Lesotho, external debt drives financial development. In addition, for Lesotho, external debt also drives investment.